2018
DOI: 10.4236/aad.2018.74010
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Yokukansankachimpihange for Treating Behavioral and Psychological Symptoms of Dementia in Patients with Alzheimer’s Disease: An Open-Label Pilot Study

Abstract: Previous clinical trials have demonstrated the efficacy of yokukansan, a traditional Japanese medicine, for the treatment of behavioral and psychological symptoms of dementia (BPSD). However, less evidence is available for the treatment of BPSD with yokukansankachimpihange (YKSCH), which consists of yokukansan and two additional herbal ingredients. The present study was conducted to investigate the efficacy and safety of YKSCH for treating BPSD in patients with Alzheimer's disease (AD). We enrolled outpatients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In addition to traditional use, YKSCH has been approved for administration to patients with dementia in Japan to treat behavioral and psychological symptoms of dementia (BPSD). A recent clinical trial revealed that YKSCH treatment improves the Neuropsychiatric Inventory scores of "agitation, " "delusion, " and "sleep and night-time behavior change" in patients with Alzheimer's disease (1). Other research revealed that a combination treatment of YKSCH with donepezil improved diurnal rhythm in patients with Alzheimer's disease (2).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to traditional use, YKSCH has been approved for administration to patients with dementia in Japan to treat behavioral and psychological symptoms of dementia (BPSD). A recent clinical trial revealed that YKSCH treatment improves the Neuropsychiatric Inventory scores of "agitation, " "delusion, " and "sleep and night-time behavior change" in patients with Alzheimer's disease (1). Other research revealed that a combination treatment of YKSCH with donepezil improved diurnal rhythm in patients with Alzheimer's disease (2).…”
Section: Introductionmentioning
confidence: 99%
“…A recent observational study showed that a combination of donepezil and YKSCH that contains Citrus reticulata instead of CPU significantly improved BPSD in patients with Alzheimer's disease, in which diurnal rhythm disturbance was significantly improved [27]. More recently, an open-label trial revealed that YKSCH tended to improve BPSD with significant improvement of apathy in Alzheimer's patients [28]. In animals, YKS and YKSCH produced the same degree of improvement in neuropsychiatric and gastrointestinal symptoms in TD rats [29].…”
Section: Introductionmentioning
confidence: 99%